School Organizational Culture and Achievement Motivation With Teacher Performance at MA Miftahul 'Ulum Tuyau School - Dewi Sinta (Indonesian Journal of Education (INJOE), 2022)
The purpose of this study was to obtain information on the correlation between school organizational culture and achievement motivation with the performance of school teachers. The approach used is quantitative with a survey method at MA Miftahul 'Ulum Tuyau. The research findings are: There is a correlation between school organizational culture and performance. 2. There is a correlation between achievement motivation and performance. 3. There is a correlation between school organizational culture and achievement motivation with performance. The results of the study implied that in school organizational culture, achievement  motivation,  quality  of performance